New topics in feminist philosophy of religion: Contestations and transcendence incarnate - Anderson, P (Springer Netherlands, 2010)
Having enjoyed more than a decade of lively critique and creativity, feminist philosophy of religion continues to be a vital field of inquiry. New Topics in Feminist Philosophy of Religion maintains this vitality with both women and men, from their own distinctive social and material locations, contributing critically to the rich traditions in philosophy of religion. The twenty contributors open up new possibilities for spiritual practice, while contesting the gender-bias of traditional concepts in the field: the old models of human and divine will no longer 'simply do'! A lively current debate develops in re-imagining and revaluing transcendence in terms of body, space and self-other relations. This collection is an excellent source for courses in feminist philosophy, phenomenology, hermeneutics and literature, Continental and analytical philosophy of religion, engaging with a range of religions and philosophers including Kant, Kierkegaard, Marx, Heidegger, Arendt, Weil, Beauvoir, Merleau-Ponty, Ricoeur, Levinas, Irigaray, Bourdieu, Kristeva, Le Doeuff, bell hooks and Jantzen. © Springer Science+Business Media B.V. 2010.